Towards a Kantian Moral Psychology or the Practical Effects of Self-Predicating Judgements of Sublimity. Issue 1 (1st February 2015) - Jaffe, Aaron
Abstract This essay develops an account of the link between Kant's aesthetics and his ethics. It does so by articulating a Kantian account of moral psychology by way of aesthetic reflective judgements of sublimity. Since judgements of sublimity enrich the picture of a Kantian subject by forcefully revealing the unbounded power of the faculty of reason, I investigate the possibility that judgements of this kind could serve as a basis for moral motivation. The paper first shows how judgements of sublimity help a subject recognize reason's unbounded nature, and proceeds to analyse the practical effects of a subject judging itself sublime. When judgements of sublimity have as their object the unbounded and unsythesizable power of reason, they may thereby serve as the basis for both the recognition of our moral vocation, and the grounds for determining the will to act from respect for it. Since a judgement of sublimity produces for Kant the experience of an enlivening emotion and an outflowing of vital forces, the paper then develops Kant's concept of "life" motivated by a recognition of its practical orientation. In this way sublimity rather than beauty can be interpreted as symbolic hypotyposis of morality. The paper then takes up less favourable interpretations of the practical effects of self-predicated judgements of sublimity, and constructs critical responses to such positions. I conclude, following Adorno, by stressing the historical and social dimension of the capacities for both making sublime judgements, and being morally enlivened by them.